Development of Vibration Measurement System using a Microcontroller - Koji Sekine; Keigo Hayakawa (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2022)
It is important to interpret resonance in the design to reduce the vibration of mechanical structures, and to verify this resonance phenomenon by experiments and theoretical approach. When the vibration of a continuous system is observed using a vibration system, the experience and skill of the observer affect the measurement accuracy of the natural frequency and vibration modes. Therefore, in this study, a vibration measurement system is developed to stably and quantitatively verify the natural vibration of the beams using a microcontroller and an ultrasonic sensor. The vibration measurement system consists of a microcontroller, a vibration motor and an ultrasonic sensor. The accuracy and validity of the natural frequencies of the beams measured by the system are discussed, and the performance of present system is evaluated on the basis of the measurement results of the natural frequencies and the natural vibration waveforms.